Beyond the ‘genius of suffering’: the paradox of an alienated border regime - refugee integration in cross-border Dagana (Senegal-Mauritania) - Tandia, Aboubakr (2013)
This article explores the nature and role of border regimes from the perspective of refugee regimes and integration. It looks at refugees as part of a border people whose agency informs the close relationship between border and refugee regimes. It analyses the transformative potential and achievements of refugee practices in local integration and their effects on borders and on refugee regimes. Focusing on the experience of a refugee community based in the cross-border zone of Dagana between Senegal and Mauritania, it contends that refugees are agentless even in the context of a rigid boundary regime. On the contrary, as authentic and legitimate actors of local integration, refugees participate in the transformation of host communities and the border regions they live in.